Implementation of Web-Based Monitoring for the Evaluation of the Performance of Intern Students at BPJS Ketenagakerjaan Medan Kota - Dewi Ragil; Megaputri Nathalina Panjaitan; Syifa Khairunisa; Reinata Carolina Widia Pasaribu; Fadillah Emilia Nasution; Ruth Grace Arlyana Manurung; Rifqi Jabrah Rhae; Habieb Pahlevi; Dr Colum A. Foley; Eka Evriza (CV Media Inti Teknologi, 2025)
Background of Study: Internship programs are essential in connecting academic knowledge with real-world work experience. However, conventional monitoring systems used during internships often lack efficiency and transparency, especially in public institutions like BPJS Ketenagakerjaan Medan Kota. Aims and Scope of Paper: This study aims to design and implement a web-based monitoring system to evaluate the performance of internship students at BPJS Ketenagakerjaan Medan Kota. The system is expected to streamline documentation, reporting, and assessment processes during the internship period. Methods: A qualitative descriptive method with a case study approach was used. Data were collected through participatory observation, in-depth interviews with mentors and students, and documentation analysis. The system was developed using Laravel, Tailwind CSS, and MySQL, then tested on a limited group of users. Result: The results showed that the system improved performance tracking, enhanced documentation of student tasks, and facilitated real-time evaluations. Users reported high satisfaction with the system's usability and clarity. Automatic score recap features and digital proof uploads made evaluation more objective and structured. Conclusion: The web-based monitoring platform has positively impacted the supervision and evaluation process of intern students. It offers a scalable solution for internship performance evaluation and has the potential to be applied in similar organizational contexts with further system enhancements.